Towards Panopticons of Convenience: Power in the Nordic Smart Home Assemblage - Ehrenberg Nils; Harviainen J. Tuomas; Suominen Jaakko (United States, 2025)
The introduction of smart home technologies shifts the social relationships in the home by replacing parts of the home assemblage with digital components. This article makes two contributions, first it analyses the influence of panopticons of convenience, which it conceptualises as ‘The acceptance of additional surveillance upon one's life for the purpose of acquiring actual or presumed convenience’ in smart homes. Second, through an empirical expert interview study it identifies several examples of how intentions and implementations of smart home technologies facilitate behaviours that cause or reinforce inequalities in the home. These examples are then used to understand how the panopticons of convenience contribute to the abjection of the less tech-savvy residents of these homes and to reflect on how these technologies shape energy consumption in the home.
Proceedings of the 26th International Academic Mindtrek Conference